Biodiversity and distribution of termite nests in West Papua, Indonesia - NIKEN SUBEKTI; ISMA NURVAIZAH; JAN HENDRIEK NUNAKI; HENGKY LUKAS WAMBRAU (Society for Indonesian Biodiversity, 2018)
Subekti N, Nurvaizah I, Nunaki JN, Wambrau HK, Mar’ah R. 2018. Biodiversity and distribution of termite nests in West Papua, Indonesia. Biodiversitas 19: 1659-1664. Termites play an important role in plant nutritive cycles by contributing to the disintegration and decomposition of organic matter. However, termites also cause damage to wood in nature as well as in buildings. Therefore, termites are potential pests and need to be controlled. Effective control of termites requires knowledge about their species prevalence and distribution. The current study aimed to identify the termite species and nest distributions in West Papua. A survey to determine the distribution of termite nests used the transect line method with intervals of 50 m in width and length. The results showed that there were 35 termite nests on 10 host trees species, namely Calophyllum inophyllum (Bintanggur), Mastixiodendron pachyclados (Lancat), Intsia bijuga (Kayu besi), Inocarpus fagifer (Gayang), Canarium hirsutum (Kenari), Horsfieldia parviflora (Pala hutan), Diospyros papuana (Black wood), Aleurites moluccana (Kemiri), Pometia coreacea (Matoa), and Vatica rassak (Resak). These nests harbored three termite genera, including Microcerotermes, Longipeditermes, and Bulbitermes. Microcerotermes were the most commonly found and had a wide distribution across almost all points of observation.